Pandemi Covid-19 Sebagai Bentuk Overmacht Terjadinya Wanprestasi Kredit di Bank - Mual, Yansen; Tjoanda, Merry; Pariela, Marselo Valentino Geovani (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The impact of Covid-19 is the weakening of the Indonesian economy, due to restrictions on activities in the business sector which show the majority of the implementation of the rights and obligations in the agreement.Purposes of the Research:  The purpose of this study is to find out whether the Covid-19 Pandemic is a Form of Overmacht Credit Default in Banking and How is Credit Default Settled Due to the Covid-19 Pandemic in Banking.Methods of the Research: The research method used is normative juridical research or literature study with a descriptive analytical research type which is a method that functions to describe or provide an overview of the object under study through legal sources.Results of the Research: The results of the research carried out must be understood that three things must be checked so that the persuasive situation clause can be applied. First, the facts must be beyond the control of the parties. Second, the ability of the parties to carry out their contractual obligations cannot be carried out due to the event that hinders them. Third, the parties have taken all steps to try to mitigate the risks that arise as a result of the event or the occurrence of such compelling circumstances. In the context of the spread of Covid-19, the first and second criteria of coercion can be said to have been met. The reason is that Covid-19 directly or indirectly has an impact on the performance and capacity of the parties so that it affects the ability to fulfill the agreement contained in the contract.